The Role of Probation and Parole Officers in Legal Reform in Indonesia: Addressing Overcrowding in Prisons and Detention Centers - Purwani, Marhaeni Sekar Fajar; Saefudin, Wahyu; Nasirudin; Budiyanto, Sigit (Restorative : Journal of Indonesian Probation and Parole System, 2024)
Abstract. Legal reform is a crucial element in maintaining justice, sustainability, and progress within a nation. In Indonesia, legal reform involves various stakeholders, including Probation and Parole Officers, who play a pivotal role in shaping a law-abiding society and supporting the implementation of a legal system grounded in restorative justice. This research aims to analyze the role of probation and parole officers in legal reform in Indonesia, particularly after the enactment of Act Number 22 of 2022 on Corrections and Act Number 1 of 2023 on the Criminal Code. The research methodology is literature review in order to explore in depth the strategic role of Probation and Parole Officers. The research findings reveal that the Act Number 22 of 2022 reinforces the role of Probation and Parole Officers through the Social Research, Guidance, Monitoring, and Assistance programs, especially in relation to reducing overcrowding in correctional facilities (Lapas) and detention centers (Rutan). The humanistic approach used, such as rehabilitation programs recommendations designed on a personal basis, aim to reform the attitude and behaviour of inmates and prepare them for social reintegration. Meanwhile, the Act Number 1 of 2023 on the new Criminal Code expands the role of Probation and Parole Officers in conducting Social Research on adult suspects, as well as providing guidance and monitoring during the supervisory sentence and social work sentence. Not only does this role reduce criminality and increase legal compliance, but it also increases the sense of justice within the society. Therefore, these two Acts serve as a strong legal basis for Probation and Parole Officers to perform their role optimally within the legal reform in Indonesia. A full support from the government and other related institutions is required to ensure the effectiveness and sustainability of this strategic role in creating a legal system that is fair, humanist, and oriented towards social restoration.